Dust ebook - Cornwell, Patricia (Kay Scarpetta, 2013)
In this novel of “nail-biting suspense” ( The Boston Globe ) from #1 New York Times bestselling author Patricia Cornwell, Kay Scarpetta is thrust deep into the dark world of designer drugs, drone technology, organized crime, and shocking corruption at the highest levels. IN DEVELOPMENT AS THE ORIGINAL SERIES SCARPETTA STARRING NICOLE KIDMAN AND JAMIE LEE CURTIS   A body, oddly draped in an unusual cloth, has just been discovered inside the sheltered gates of MIT, and it’s suspected the identity is that of missing computer engineering grad student Gail Shipton, last seen the night before at a trendy Cambridge bar. It appears she’s been murdered, mere weeks before the trial in her $100 million lawsuit against her former financial manager, and Massachusetts Chief Medical Examiner Kay Scarpetta doubts it’s a coincidence. She also fears the case may have a connection with her computer genius niece, Lucy.   At a glance there is no sign of what killed Gail Shipton, but she’s covered with a fine dust that under ultraviolet light fluoresces brilliantly in three vivid colors, what Scarpetta calls a mineral fingerprint. Clearly the body has been posed with chilling premeditation that is symbolic and meant to shock, and Scarpetta worries that the person responsible is the Capital Murderer, whose most recent sexual homicides have terrorized Washington, D.C.   In Dust , Scarpetta and her colleagues are up against a force far more sinister than a sexual predator who fits the criminal classification of a “spectacle killer.” With unparalleled high-tension suspense and the latest in forensic technology, Patricia Cornwell once again proves her exceptional ability to surprise—and to thrill.